THE ANALYSIS OF ENGLISH TEACHERS PROBLEMS FACED IN IMPLEMENTING OF TEAM TEACHING - Muthmainnah Mursidin; Jusmaniar N (Fakultas Keguruan dan Ilmu Penidikan UIM, 2020)
ABSTRACT: The Analysis of English Teachers Problems Faced in Implementing of Team Teaching. This study aimed to find out the problems faced by the English teachers implement team teaching at SMP Negeri 2 RSBI Maros. This study employed a descriptive – qualitative method, because it was designed to describe the implementation of English team teaching SMP Negeri 2 RSBI Maros in the form of words rather than numbers. The subject of this research was the English teachers. There were two English teachers as subjects implemented team teaching. The data were collected through observation checklist and interview. There were some important points in observation checklist and in the interview that researcher used to find out the research questions in this research. The result of the observation checklist showed that all the team teachers shared all the activities in team teaching from planning, implementation until evaluation in different roles and responsibilities in implementing team teaching and they did all the activities of team teaching in the classroom was very responsible and the result of interview showed the team teachers discussed and worked together in every phase in teaching and learning process. The team teachers built up a good communication in team teaching in the classroom. The clear communication is important thing in implementing team teaching to solve some problems faced implementing team teaching in teaching English.Key Words: English teacher, problem faced, team teaching,